The year of disappearances - Hubbard, Susan (New York : Simon & Schuster, 2008)
Ariella Montero is half-human, half-vampire. It seems wherever she goes people either disappear or are murdered. In contending with the politics of vampire and human cultures, she continues her quest to recognize the demons who may live inside us so that they can be removed.
"A novel"--Cover.
Sequel to: Society of S.
Keywords: Vampires -- Fiction; Murder -- Fiction; Disappeared persons -- Fiction; Montero, Ariella (Fictitious character) -- Fiction; Horror fiction